"Dipiao", Chinese approach to transfer of land development rights: The experiences of Chongqing. (December 2020) - Chen, Chun; Yu, Li; Choguill, Charles L.
Highlights: Provision of land for urban development and the protection of cultivated land has been a dilemma in Chinese urbanization. Dipiao, a development rights transfer mechanism intends to address dilemma of Chinese urbanization. Dipiao mechanism promote urban rural integration. Mechanism of Dipiao is able to improve land use efficiency, protect rural land, and increase peasants' income. Some factors, e.g. higher cost, uncertainty, and others affect effective and efficient delivery of Dipiao in Chongqing. Abstract: A contradictory policy in Chinese rapid urbanization comes from the twin demands for urban development land uses due to urban expansion and the protection of cultivated land for food security. Dipiao, a type of development rights transfer in Chongqing, aims at protecting cultivated land, optimizing the urban-rural land use structure, increasing villagers' income and easing the tensions between cultivated land protection and urban land development. The mechanism of Dipiao seems to be a solution to address the Chinese dilemma of land uses in urbanization. However, after delivery of this mechanism for 4 years, the market of Dipiao began to fall, especially on the demand side. The purpose of this paper is to study the determinant factors, including higher cost, uncertainty and decreases in benefits, developers' unfulfilled expectations, and accessibility to alternatives, that affect the market of Dipiao . It is expected that this research may offer some inspiration to government policy makers to reduce transitional costs in the Dipiao mechanism.